The comparison of biodistribution of glutathione PEGylated nanoliposomal doxorubicin formulations prepared by pre‐insertion and post‐insertion methods for brain delivery in normal mice - Amin Mehrabian; Saba Dadpour; Mohammad Mashreghi; Javad Zarqi; Anis Askarizadeh; Ali Badiee; Leila Arabi; Seyedeh Alia Moosavian; Mahmoud Reza Jaafari (IET Nanobiotechnology)
Abstract Several obstacles limit the efficacy of brain tumour treatment, most notably the blood‐brain barrier (BBB), which prevents the brain uptake of the majority of accessible medicines due to tight junctions. The presence of glutathione (GSH) receptors on the BBB surface has been demonstrated in numerous papers; consequently, products containing glutathione as a targeting ligand coupled with nanoliposomes are used to enhance drug delivery across the BBB. Here, the 5% pre‐inserted PEG2000‐GSH PEGylated liposomal doxorubicin was conducted according to 2B3‐101 being tested in clinical trials. In addition, PEGylated nanoliposomal doxorubicin connected to the spacer‐GSH targeting ligand (GSGGCE) and the PEG3400 was conducted using post‐insertion method. Next, in vivo biodistribution of the produced formulations was tested on healthy mice to see if GSGGCE, as the targeted ligand, could cross the BBB compared to 5% pre‐inserted PEG2000‐GSH and Caelyx®. Compared to the pre‐inserted formulation and Caelyx®, the post‐inserted formulations' concentration was lower in the heart and higher in brain tissues, resulting in boosting the brain concentration of accumulated doxorubicin with fewer possible side effects, including cardiotoxicity. In comparison to the pre‐insertion procedure, the post‐insertion method is easier, faster, and more cost‐effective. Moreover, employing PEG3400 and the post‐insertion approach in the PEG3400‐GSGGCE liposomal formulations was found to be effective in crossing the BBB.